THE EFFECT OF DEBT TO EQUITY RATIO, RETURN ON ASSETS AND INFLATION ON STOCK PRICES OF OIL AND GAS MINING COMPANIES 2014-2019 - Mega Rizki Amaliah; Gusganda Suria Manda (Jurnal Riset Akuntansi Terpadu, 2021)
This study aims to examine the effect of the variable Debt to Equity Ratio, Return On Assets, and Inflation on the Stock Price of oil and gas mining companies. The population in this study were 9 companies that are members of the oil and gas mining sub-sector in 2014-2019. While the sample used is 6 companies using purposive sampling technique. This research also uses secondary data, multiple linear regression analysis, descriptive statistics, classical assumption test, partial test, simultaneous test and R square test of determination. The results obtained state that DER, ROA, inflation partially or simultaneously these three variables have no effect on stock prices.